2004
DOI: 10.1016/j.ejca.2004.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for catheter-related thrombosis in cancer patients

Abstract: We investigated the risk factors for venous thrombosis in cancer patients with implantable ports undergoing chemotherapy. One hundred and seventy one ports were placed in a central (''chest ports'') and 84 in a peripheral vein (''arm ports''), 181 received prophylactic nadroparin and 10 coumarin. Clinically overt thrombosis was confirmed by ultrasound or angiography. Catheter-related thrombosis incidence without anticoagulants was 28% in arm and 33% in chest ports, but with anticoagulants this was 32% in arm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
1
11

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 27 publications
2
72
1
11
Order By: Relevance
“…There was a report that risk factors for thrombosis included >1 insertion attempts (26). However, tumor type, disease stage, platelet count, number of chemotherapeutic cycles or types of chemotherapy were not found to be associated with thrombosis (27). Based on earlier studies, in which a high incidence of catheter-related thrombosis was reported, several studies have been conducted regarding the use of thrombosis prophylaxis in these patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…There was a report that risk factors for thrombosis included >1 insertion attempts (26). However, tumor type, disease stage, platelet count, number of chemotherapeutic cycles or types of chemotherapy were not found to be associated with thrombosis (27). Based on earlier studies, in which a high incidence of catheter-related thrombosis was reported, several studies have been conducted regarding the use of thrombosis prophylaxis in these patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, total parenteral nutrition, chemotherapy and other drugs infused through the CVC may exacerbate any local areas of vessel wall damage (Baglin and Boughton, 1986). Cancer patients with constitutional thrombophilias (notably antithrombin deficiency) appear to be at an increased risk of CVC-related thrombosis, (De Cicco et al, 1995;Tesselaar et al, 2004) as do those with elevated homocysteine levels, but not those with the factor V Leiden or prothrombin 20210A gene mutations (De Cicco et al, 1995;Tesselaar et al, 2004). Ovarian carcinoma has also been associated with a higher incidence of CVC-related venous thrombosis compared to other tumour types (Tesselaar et al, 2004).…”
mentioning
confidence: 99%
“…26 Nor did we find support for left-sided insertion site and hereditary thrombophilia being risk factors for CVC-associated thrombosis as reported by Tesselaar et al 19 Hereditary thrombophilia has not been assessed routinely in our patients, and the impact of the CVC insertion site was probably overshadowed in the multivariate analysis by the presence of persistent CoNS bacteraemia as these two variables were highly associated with one another.…”
Section: Discussionmentioning
confidence: 37%
“…16 The incidence of catheter-associated thrombosis was relatively high (9.5%), and is in the same range as found in prospective studies and retrospective studies of SCT recipients. [17][18][19][20] However, lower incidences have also been reported, although the use of prophylactic anticoagulants for CVC thrombosis might have influenced these results. [21][22][23] We found the use of TBI, occurrence of persistent CoNS bacteraemia and a positive catheter-tip culture-an indication of catheter colonisation-as the strongest risk factors for CVC-associated thrombosis.…”
Section: Discussionmentioning
confidence: 96%